UPACARA ADAT RAMBU SOLO: RAMBU SOLO - Aulia, Guruh Ryan (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2022)
Culture is an integrated part of people's lives. There is no community life that does not has a culture as part of their characteristics. They are known as a community group that is different from other groups, tribes, or nations. Culture also has a system of ideas that guides every human being in carrying out their lives both individually and in groups. Toraja culture, in this case the Rambu Solo Traditional Ceremony, is caused by a standard that is guided by individuals and groups that have been maintained, accepted, owned, and inherited by the Toraja people. The traditional of Rambu Solo ceremony for the people of Tana Toraja is a traditional ceremony and funeral that requires the family of the deceased to make a party as a sign of final respect for the departed deceased. Traditional ceremonies and funerals require the family of the deceased to make a party as a sign of final respect for the departed deceased. Keywords; Rambu Solo Ceremonies; Culture; Tana Toraja